Inaccuracy in foreign trade statistics of LDCs: The case of the ASEAN area - M. Kostecki; M. Tymowski (Intereconomics, 1984)
The foreign trade statistics of developing countries are relatively abundant and generally considered more reliable than data on their national accounts. This study reports the results of an accuracy test applied to export and import data from five developing countries (Indonesia, Malaysia, the Philippines, Singapore and Thailand), all members of ASEAN, a grouping which offers a particularly interesting sample of developing countries for this type of investigation.
Keywords: 330